ANALISIS PERTIMBANGAN HAKIM DALAM MENGABULKAN BANDING TERDAKWA PERKARA PEMBUNUHAN BERENCANA DENGAN MUTILASI BERDASARKAN KUHAP - Angel Julisya Uneka Sari Tanjung; Bambang Santoso (Sebelas Maret University, 2025)
This article analyzed the criminal procedure law regarding the filing of an appeal by the defendant against the death penalty verdict granted by the Court of Appeal in the case of premeditated murder with mutilation. The Judge of the Court of Appeal concurred with the Judge of the Court of First Instance that the defendants were legally and convincingly proven guilty of committing the crime in the primary charge. However, the Judge of the Court of Appeal granted the appeal due to his dissent regarding the length of the sentence given. This article aimed to determine if the High Court Judge's verdict to grant the defendant's appeal adhered to the stipulations outlined in the Criminal Procedure Code. The research method used was normative legal research, which was prescriptive and applied. The legal materials were collected using literature studies, and the legal materials used were primary and secondary. Based on the research and discussion of the problem, it can be concluded that the High Court Judge's consideration of granting the appeal filed by the defendant was in line with the provisions of the Criminal Procedure Code.